2007
DOI: 10.1677/jme.1.02138
|View full text |Cite
|
Sign up to set email alerts
|

Npr1-regulated gene pathways contributing to cardiac hypertrophy and fibrosis

Abstract: The natriuretic peptides, atrial (ANP) and brain natriuretic peptide (BNP) are known to suppress cardiac hypertrophy and fibrosis. Both ANP and BNP exert their bioactivities through the Npr1 receptor, and Npr1 knockout mice (Npr1K/K) exhibit marked cardiac hypertrophy and fibrosis. In this study, we investigated which genes within the hypertrophic and fibrotic pathways are influenced by the lack of Npr1 signalling. cDNA microarray and quantitative real-time PCR (RT-PCR) analyses were performed on cardiac ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 32 publications
3
80
2
Order By: Relevance
“…Mean arterial blood pressure (MAP) was calculated from systolic and diastolic readings obtained by a noninvasive, computerized tail-cuff system (ADInstruments, Dunedin, New Zealand) as previously described (10). The mice were familiarized to the procedure by being placed briefly in a restrainer and the tail cuff system over a period of 7 days, after which baseline MAP measurements were made for each animal (mean of Ն10 recordings).…”
Section: Methodsmentioning
confidence: 99%
“…Mean arterial blood pressure (MAP) was calculated from systolic and diastolic readings obtained by a noninvasive, computerized tail-cuff system (ADInstruments, Dunedin, New Zealand) as previously described (10). The mice were familiarized to the procedure by being placed briefly in a restrainer and the tail cuff system over a period of 7 days, after which baseline MAP measurements were made for each animal (mean of Ն10 recordings).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, Class II HDACs may also be involved in the pathogenesis of cardiac hypertrophy. In a study investigating the action of natriuretic peptide receptor-A-induced cardiac hypertrophy and fibrosis, Ellmers et al (2007) demonstrated that HDAC 7a mRNA expression was increased in natriuretic peptide receptor-A knockout mice at a more advanced stage, followed by increased TGF ␤1 and other structural molecules associated with cardiac fibrosis such as collagen I. Atrial interstitial fibrosis is a significant factor driving arrhythmia genesis and is highly prevalent in heart failure and cardiac hypertrophy (Verheule et al, 2004). Atrial fibrosis influences the development of atrial fibrillation, particularly in the setting of structural heart disease where angiotensin-inhibition is partially effective in reducing atrial fibrosis and atrial fibrillation.…”
Section: The Role Of Hdacs In Cardiac Hypotrophy and Fibrosismentioning
confidence: 99%
“…The ANP/NPRA system elicits natriuretic, diuretic, vasorelaxant, and antiproliferative responses, all of which contribute largely to the reduction of blood pressure and blood volume (40,49,64). Previous studies have suggested that NPRA signaling is involved not only in maintaining the arterial pressure but also in antagonizing the cardiac growth responses to hypertrophic stimuli (6,14,34). It has been shown that both external and internal stimuli regulate Npr1 (coding for GC-A/ NPRA) expression and receptor signaling, including angiotensin II (ANG II), all-trans retinoic acid (RA), vitamin D, and extracellular osmolality (1,8,16,21).…”
mentioning
confidence: 99%
“…Previous studies have suggested that ANP/ NPRA signaling acts as a negative regulator of inflammation and hypertrophic growth (14,65,67,69). However, the studies on the role of ANP/NPRA in regulating the expression of hypertrophic and proinflammatory markers in vivo are limited.…”
mentioning
confidence: 99%